Reverse tube direction and epistaxis in left nasotracheal intubation: a randomized controlled trial - Jun-Young Park; Jihion Yu; Chan-Sik Kim; Taeho Mun; Woo Shik Jeong; Jong Woo Choi; Kichang Lee; Young-Kug Kim (Korean Journal of Anesthesiology)
Background The incidence of epistaxis during nasotracheal intubation via the left nostril is more frequent than that during intubation via the right nostril. This study evaluated the effect of the reverse bevel and tip direction of the nasotracheal tube on the incidence of epistaxis during nasotracheal intubation via the left nostril. Methods Patients undergoing right-sided maxillofacial surgery requiring left nasotracheal intubation were randomly allocated to the control (tracheal tube in the conventional direction) or reverse (a 180˚ reverse direction, with the tube bevel facing the nasal septum and the leading edge (i.e., the tip) of the bevel pointing away from the nasal septum) groups (n = 37 for both). The primary outcome was the incidence of epistaxis evaluated using videolaryngoscopy. Results The incidence of epistaxis in the reverse group was significantly lower than that in the control group (9 [24.3%] vs. 20 [54.1%], P = 0.009; relative risk: 0.45, 95% CI [0.24, 0.85], absolute risk reduction: 29.8%, number needed to treat: 3). The severity of epistaxis was significantly lower in the reverse group (P = 0.002). The first attempt nasal passage (P = 0.027) was significantly higher in the reverse group. Postoperative nasal pain was lower (P < 0.001), and patient satisfaction was higher (P < 0.001) in the reverse group. Nasotracheal tube-related complications did not occur in either group. Conclusions The reverse bevel and tip direction of the nasotracheal tube reduced the incidence and severity of epistaxis and increased patient satisfaction among patients undergoing left nasotracheal intubation.